PocketSkills: A Conversational Mobile Web App to Support Dialectical Behavioral Therapy - Schoeder, Jessica; Wilks, Chelsey; Rowan, Kael; Toledo, Arturo; Paradiso, Ann; Czerwinski, Mary; Mark, Gloria; Linehan, Marsha M. (In Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems (CHI ’18), 2018)
Mental health disorders are a leading cause of disability worldwide. Although evidence-based psychotherapy is effective, engagement from such programs can be low. Mobile apps have the potential to help engage and support people in their therapy. We developed Pocket Skills, a mobile web app based on Dialectical Behavior Therapy (DBT). Pocket Skills teaches DBT via a conversational agent modeled on Marsha Linehan, who developed DBT. We examined the feasibility of Pocket Skills in a 4-week field study with 73 individuals enrolled in psychotherapy. After the study, participants reported decreased depression and anxiety and increased DBT skills use. We present a model based on qualitative findings of how Pocket Skills supported DBT. Pocket Skills helped participants engage in their DBT and practice and implement skills in their environmental context, which enabled them to see the results of using their DBT skills and increase their self-efficacy. We discuss the design implications of these findings for future mobile mental health systems.